SISTEM INFORMASI PENGIRIMAN BARANG BERBASIS WEBSITE (STUDI KASUS: PT JASTIPMAN JAKARTA KE ANAMBAS KEPULAUAN RIAU) - Betesda .; Jehan Saptia Kurnia (Fakultas Ilmu Komputer dan Desain - Unsurya, 2024)
PT. Jastipman Jakarta to Anambas Islands in Riau is a company engaged in the delivery service industry. The use of manual recording systems in the delivery process has a significant impact on the company's performance and customer satisfaction. As a company providing delivery services, all activities must always be timely and there should be no delays in the services provided, especially in the delivery process. The research method used in creating this proposal report is through observation directly at the research site, and the Waterfall method is a basic process that involves specification, development, validation, solution, and represents it as different process phases such as specification requirements, software design, implementation, and testing. The system design will be explained in the proposed system procedures, the proposed system procedures will be implemented using UML, the database design, the proposed system interface design, the proposed system configuration, the proposed implementation, and blackbox testing. The implementation of an information system for delivery services can improve the company's performance by making the delivery process easier to process and making it easier for customers to obtain information about their shipment through the tracking feature using the provided tracking number. Â Keyword: System, Information System, Shipping Information System.